(untitled) (Research, Society and Development, 2025)
Objective: To evaluate the effectiveness of the Manchester Triage System in risk prioritization of patients seeking the Oncology Emergency Service with complaints of pain. Methods: This is a retrospective, cross-sectional, and quantitative study conducted in São Paulo, Brazil. Patients presenting with pain between February and April 2022 were included. Data were collected through analysis of the Electronic Medical Record. The sample consisted of 1,662 participants. Results were analyzed using Pearson’s Chi-square test and Fisher’s Exact test, with a significance level of 5%. Results: A total of 1,662 patients participated, with a mean age of 57.9 years, mostly female, with upper digestive tract cancer (19.8%) and breast cancer (17.6%). Most were not using opioids (69.3%) and were discharged as a clinical outcome (72.4%). The Manchester Triage System (MTS) categories showed a majority using the adult abdominal pain flowchart (27.5%), with a discriminator for mild pain (63.1%) and classified as low-urgency priority (67.3%). A statistically significant association was observed between the flowchart and discriminator of the MTS and the use of opioids (p ≤ 0.05). Conclusion: Most cancer patients presenting with pain in the Oncology Emergency Service were not using opioids, were triaged as low urgency, reported mild to moderate pain, followed the adult abdominal pain flowchart, and were discharged. A statistically significant association was found between the MTS flowchart and discriminator and opioid use, indicating a relationship between triage and treatment.